Segmentation of Indian shoppers based on store attributes. (20th July 2009) - Hemalatha, M.; Sivakumar, V.J.; Jayakumar, G.S. David Sam
Different groups of consumers believe that different store attributes are important. Therefore, store attributes appears to be a promising market segmentation criterion. In this sense, the present work focuses on store attributes as a possible criterion to segment the shoppers. It starts by analysing the importance of consumer segmentation to the retailers. After reviewing the literature of market segmentation, we performed a segmentation analysis of clothing and apparel shoppers in India. First, a hierarchical cluster analysis was carried out, and then k-means cluster analysis identified three meaningfully differentiated customer groups. Further, a classification tree analysis was performed to identify the store attributes that differentiated the clustered groups. Finally, three clusters of Indian shoppers, namely, economic shoppers, convenient shoppers and elegant shoppers are identified. Main conclusions and its implications for retailing management are pointed out. Our concern in this paper is to understand the Indian shoppers and segment them based on the shopper's perception on store attributes.